Grass Roots: African Origins of an American Art - Anderson, E. N. (Ethnobiology Letters, 2010)
Review of Grass Roots: African Origins of an American Art. Dale Rosengarten, Theodore Rosengarten, and Enid Schildkrout, eds. 2008. Museum for African Art, New York. Distributed by University of Washington Press, Seattle. Pp. 269, copiously illustrated in black-and-white and color. ISBN (cloth) 978-0-945802-50-1, (paper) 978-0-945802-51-8.